PENDAMPINGAN UPDATE PROFIL SINTA DOSEN DI FAKULTAS PERTANIAN DAN FAKULTAS KEDOKTERAN UNIVERSITAS METHODIST INDONESIA - Jamaluddin Jamaluddin; Gortap Lumbantoruan; Eviyanti N. Purba; Arthur Simanjuntak; Doli Hasibuan; Roni Jhonson Simamora; Lince R. Panataria; Endi Juli Anto (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community service is part of the tridarma task of higher education. This community service activity leads to the application of knowledge and technology directly to the community. In this community service activity, the team provided assistance to fellow Methodist Indonesia University lecturers at the Faculty of Medicine and Faculty of Agriculture. This activity aims to assist fellow lecturers in the two Faculties in updating the SINTA profile of each lecturer based on the existing circular letter.